1999
DOI: 10.1097/00002030-199910010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of subtype A HIV-1 from Africa by full genome sequencing

Abstract: The prevailing view of HIV-1 subtype A forming a uniform band across the center of sub-Saharan Africa needs revision. In all probability, the most common subtype in west Africa and west central Africa is the AG recombinant, AG(IbNG), whereas in east central Africa it is the non-recombinant subtype A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
2

Year Published

2000
2000
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 18 publications
2
46
0
2
Order By: Relevance
“…It is subtype A in the gag gene and the majority of the env gene, subtype G in the long terminal repeats, and a mosaic of A and G in the pol gene. It is epidemic in West and West Central Africa (3,27) and is the predominant virus circulating in Senegal (38). The CRF02_A/G-IbNG-infected individuals included in our study were antiretroviral therapy-naïve at the time of sampling.…”
mentioning
confidence: 99%
“…It is subtype A in the gag gene and the majority of the env gene, subtype G in the long terminal repeats, and a mosaic of A and G in the pol gene. It is epidemic in West and West Central Africa (3,27) and is the predominant virus circulating in Senegal (38). The CRF02_A/G-IbNG-infected individuals included in our study were antiretroviral therapy-naïve at the time of sampling.…”
mentioning
confidence: 99%
“…In areas where multiple subtypes cocirculate, it is estimated that intersubtype recombinant sequences (ISRs) account for between 8 and 24% of infections (23). Senegal has a high prevalence of CRF02AG infections (4,24,25,30,32) and recombination with this form of the virus could have been predicted. Given that subtype A viruses have been identified in a majority of the circulating intersubtype recombinants, as well as both intergroup (M/O) recombinants (10,20,24), it is also not surprising to find that the HIV-1 A3 viruses are involved in recombination events.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly the entire genome was obtained in one continuous segment by using the nested primers MSF12b-OFMR1, for round 1, and F2nst-ofm19, for round 2, utilizing methods previously described (4,29). The amplicon was directly sequenced by using Big Dye terminators on an ABI 3100 capillary sequencer (Applied Biosystems), according to manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, CRF02_AG contributes to a major number of new infections in West Africa and appears to be associated with rapidly spreading epidemics in West African countries (3,6,7,28,31,35,37). The underlying causes of the varied geographic distributions are most likely founder effects with other contributing factors, such as human population movements, unregulated commercial sex work, and intravenous drug use.Over the course of an 18-year prospective study monitoring a cohort of female sex workers (FSWs) in Dakar, Senegal, we found that the most prevalent circulating strain in the cohort is CRF02_AG, as seen in other parts of West Africa (2,6,7,28,31,35,37). However, recent work conducted in our lab revealed that a unique group of viruses within the human immunodeficiency virus type 1 (HIV-1) subtype A radiation is also present in the FSW study population (40,42).…”
mentioning
confidence: 99%